Study on the Customer Perception of the Tropical Fruit Vinegar in Kelantan and Kuala Lumpur. Issue 3 (3rd April 2018) - Abdul Latiff, Zul Ariff; Mokhtar, Seri Intan; Soon, Siow Woon; Ayob, Mohamad Amizi
ABSTRACT: This research will be focus on the differences of perception of customers in Kelantan and Kuala Lumpur toward tropical fruits vinegar. Tropical fruit vinegar was used in this research with Rambutan and Dokong vinegar as the choice. Dokong and Rambutan are tropical seasonal fruits. The production quantity is getting higher these few years, and it results that farmers have to face all negative impact. Next, this study also reduces the import of vinegar product. Furthermore, this study also helps in fulfilling the national agenda in National Agro Food Policies 2011–2020. The amount of respondents are 108 in Kelantan and 69 in Kuala Lumpur. The major finding is Customers in Kuala Lumpur and Kelantan both accepts Natural Fruits Vinegar products. The result also shows that consumers are concern about the quality, safety, and nutritional content of products and prefer glass material for packaging than plastic material.